Social inclusion for empowering individuals and groups through Edutourism in Karangpatihan, Ponorogo - Amalia, Novi Rizka; Setiawan, Veri; Rahayu, Dini Septyana (Journal of Community Service in Science and Engineering (JoCSE), 2024)
This activity aims to support social inclusiveness in the context of individual and group empowerment. Through the Eduwisata program in Karangpatihan Village, Ponorogo, education and tourism are integrated to increase active community participation, including marginalized or vulnerable groups. Karangpatihan Village is synonymous with villages that have disabled people who are, of course, empowered and involved in various moments. The methods used to determine the success of this program are interviews, observation and document analysis. The results of this activity show that the edutourism program in Karangpatihan Village has succeeded in creating an inclusive environment that facilitates participation from all levels of society, including individuals and groups previously marginalized. This activity contributes to the understanding of social inclusion practices through an edutourism approach at the village level and provides inspiration for the development of similar programs in other regions. The practical implication is strengthening the community's capacity to improve the overall quality of life. Thus, this activity is relevant to the local context of Karangpatihan Village and can also be a reference for policymakers, practitioners and practitioners interested in efforts to increase social inclusion through education and tourism approaches at the community level. Kegiatan ini bertujuan untuk mendukung adanya inklusifitas sosial dalam konteks pemberdayaan individu dan kelompok. Melalui program Eduwisata di Desa Karangpatihan, Ponorogo, edukasi dan wisata diintegrasikan sebagai sarana untuk meningkatkan partisipasi aktif masyarakat termasuk didalamnya kelompok yang terpinggirkan atau rentan. Di Desa Karangpatihan identic dengan desa yang memiliki masyarakat disabilitas yang tentunya diberdayakan dan dilibatkan dalam berbagai momentum. Metode yang digunakan dalam menentukan keberhasilan program ini adalah wawancara, observasi, dan analisis dokumen. Hasil kegiatan ini menunjukkan bahwa program eduwisata di Desa Karangpatihan telah berhasil menciptakan lingkungan inklusif yang memfasilitasi partisipasi seluruh lapisan masyarakat, termasuk individu dan kelompok yang sebelumnya terpinggirkan. Kegiatan ini memberikan kontribusi pada pemahaman praktik inklusi sosial melalui pendekatan eduwisata di tingkat desa, serta memberikan inspirasi untuk pengembangan program serupa di wilayah lain. Implikasi praktisnya adalah penguatan kapasitas masyarakat dalam meningkatkan kualitas hidup secara keseluruhan. Dengan demikian, kegiatan ini tidak hanya relevan untuk konteks lokal Desa Karangpatihan, tetapi juga dapat menjadi acuan bagi pengambil kebijakan, praktisi, dan praktisi yang berminat dalam upaya meningkatkan inklusi sosial melalui pendekatan edukasi dan wisata di tingkat komunitas.